The effectiveness of combined Orton-Davis method as distance learning on dyslexia of dyslexic female students in elementary school in Tehran in Covid-19 Pandemic Period - Mohammadi, Shirin; Baseri, Ahmad; Mohammadi Aria, Alireza (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of the present study was to determine the effectiveness of the integrated method of Orton-Davis in the form of distance education on dyslexia of dyslexic female students in elementary school in Tehran. Methods: The research method in this study was semi-experimental and pre-test-post-test design with control group. The statistical population of this study was all the dyslexic primary school girls who attended learning disorders centers in Tehran in 2020-21. To measure the dependent variable of the study, the Nema reading and dyslexia test (Kormi Nouri and Moradi, 2014) was used. In this research, two educational interventions of the integrated Orton-Davis method, which is one of the multi-sensory methods and includes tasks based on directional games, were designed and compiled by Atchershawi (2019) to improve reading skills and reduce dyslexia. Results: The results showed that the combined method of Orton-Davis in the form of distance education on the overall performance of reading (P<0.001) and understanding words (P<0.001) and understanding the text of children (P<0.001). Conclusion: It can be concluded that the combined method of Orton-Davis in the form of distance education has an effect on the overall performance of reading and comprehension of words and text of dyslexic children and it can be used to reduce the problems of dyslexic children.